Effects of Medicare advantage on patterns of end‐of‐life care among Medicare decedents. (28th February 2022) - Park, Sungchul; Teno, Joan M.; White, Lindsay; Coe, Norma B.
Abstract: Objective: To examine the effects of Medicare Advantage (MA) enrollment on patterns of end‐of‐life care. Data sources: We used data from the Master Beneficiary Summary File, the Medicare Provider Analysis and Review, hospice claims, the Minimum Data Set, the Outcome and Assessment Information Set, the Area Health Resources File, and Geographic Variation Public Use File for 2012–2014. Study design: To address selective enrollment into MA, we exploited a discontinuity in payment rates by county population (urban floor payments) as an instrument. Data collection/extraction methods: We identified Medicare beneficiaries continuously enrolled in MA or TM during their last year of life between 2012 and 2014 using Medicare administrative data. Principal findings: We did not find evidence that MA enrollment led to a change in hospital admissions in the last 30 days of life, but MA enrollment decreased hospital as the site of death by 11.0 (95% CI: −13.9 to −8.1) percentage points. Once hospitalized, however, MA enrollment increased use of intensive care by 6.7 (95% CI: 0.3 to 13.1) percentage points and non‐invasive mechanical ventilation by 9.2 (95% CI: 5.5 to 12.9) percentage points. MA enrollment increased hospice use by 6.2 (95% CI: 2.3 to 10.1) percentage points at time of death and 7.7 (95% CI: 3.8 to 11.6) percentage points in the last 30 days of life. Particularly, MA enrollment increased hospice admissions among those who were admitted to the hospital within 30 days prior to hospice admission by 18.8 (95% CI: 13.8 to 23.8) percentage points. However, MA enrollment decreased hospice admissions among those who were admitted to home health within 30 days prior to hospice admission by 18.6 (95% CI: −21.9 to −15.2) percentage points. Conclusions: MA plans may improve end‐of‐life care by reducing hospital death while also improving access to hospice, especially among recently hospitalized persons.